Examining professionalisation in public procurement by ranking practitioner job positions according to job activities. (2016) - Steinfeld, Joshua M.; McCue, Clifford; Prier, Eric
Similar to public administration over the last couple of decades, public procurement is trying to define itself as a profession. The purpose of this manuscript is to provide a framework for analysing job positions within the occupation of public procurement and to examine the field's potential for professionalisation. The data originates from a survey of public procurement practitioners administered by the Universal Public Procurement Certification Council (UPPCC) that is intended to obtain information with regards to task and knowledge areas. Distinctions can be made between job positions that serve to rank order public procurement practitioners, which may eventually lead to an argument for professionalising the occupation. The job activities performed and managed in perhaps the fastest growing occupation within the public sector are catalogued in this study. Furthermore, practitioner membership to professional associations and attainment of certifications are analysed to test for the advent of professionalisation across job positions.